Approaches to the design of refugee camps: An empirical study in Kenya, Ethiopia, Greece, and Turkey. Issue 3 (9th March 2018) - Jahre, Marianne; Kembro, Joakim; Adjahossou, Anicet; Altay, Nezih
Abstract : Purpose: An unprecedented scale of human migration has lead humanitarians to view camps as long-term settlements rather than temporary holding facilities. The purpose of this paper is to increase the understanding of and identify challenges with this proposed new approach to camp design. Design/methodology/approach: Based on the camp design literature, the authors developed an interview guide and checklist for data collection. A multi-site case study and within- and cross-case analysis was then conducted. Findings: The findings suggest that the proposed new approach is implemented only to a limited extent, and mostly in a stepwise manner. As camps mature, there is a shift toward the new approach, but most camps are established using the traditional top-down, temporary, and isolated approach. Research limitations/implications: The findings are based on four camps in four different countries and do not provide an exhaustive global coverage. Practical implications: The insights the authors derived and the challenges identified from the empirical evidence can be used to better plan future camps. Social implications: The results can support improvements in camp design, thus alleviating suffering for both refugees and host communities, particularly in developing countries. In particular, the trade-off between a permanent solution and the temporary must be accounted for. Originality/value: The study contributes to the literature by developing and proposing a conceptual framework to camp design. The cross-case analysis provides an initial understanding and categorization of challenges with implementing the new approach. It also suggests an evolutionary perspective of camp design.